I07 Allele specific gene editing for huntington's disease mediated by the KAMICAS9 self-inactivating CRISPR/CAS9 system. (September 2018) - Deglon, Nicole; Vachey, Gabriel; Rey, Maria; Perrier, Anselme
Abstract : Huntington's disease (HD) is a fatal neurodegenerative disorder caused by CAG expansion in the huntingtin (HTT) gene. Considering that the mutation is a toxic gain-of-function, a promising approach would be to decrease the expression level of the mutant HTT. This can be achieved with genome-editing technologies, in particular the recently characterized CRISPR/Cas9 system. In a previous work, we described the kamiCas9, a self-inactivating CRISPR/Cas9 system designed for the transient expression of the Cas9 protein. We demonstrated the high editing efficiency of this system both in in vitro and in vivo HD models with an important reduction of the off-target frequency. However, a selective editing of mutant HTT, using an allele-specific approach, represents the safest way to preserve WT HTT expression and functions. We thus developed more complex strategies to discriminate mutant and wild-type HTT genes by using single-guide RNA targeting sequences containing Single Nucleotide Polymorphism (SNP) in the HTT gene. A first in vitro screening, allow us to discriminate the two best candidates to trigger the cleavage of the mutant HTT respectively in the promoter and intron 1. Through this approach the exon 1 of the mutant HTT, which is the region containing the CAG expansion, could be selective removed. These strategies have then been validated in human embryonic kidney 293T (HEK- 293T) cells and are currently tested in HD mouse models. These results demonstrate the potential of the self-inactivating CRISPR/Cas9 editing for applications in the context of neurodegenerative diseases and a proof of principle of allele specific disruption of the human HTT gene.